Ecology and conservation of North American sea ducks - Savard, Jean-Pierre L.; Derksen, Dirk V.; Esler, Dan; Eadie, John M. 1955-; Skean, Vanessa W. (CRC Press, Taylor & Francis Group, 2015)
The past decade has seen a huge increase in the interest and attention directed toward sea ducks, the Mergini tribe. This has been inspired, in large part, by the conservation concerns associated with numerical declines in several sea duck species and populations, as well as a growing appreciation for their interesting ecological attributes. Reflecting the considerable research recently conducted on this tribe, Ecology and Conservation of North American Sea Ducks examines the 15 extant species of sea ducks from North America.Chapters are organized conceptually to focus on, compare, and contras.
Keywords: Sea ducks -- Ecology -- North America.; Sea ducks -- Conservation -- North America.; elektronické knihy; electronic books